Sistem Informasi Absensi Berbasis Website Menggunakan API WhatsApp dengan Metodologi Incremental (Studi Kasus: SMP Negeri 29 Pekanbaru) - Sendy Aprilia (Journal of Applied Informatics and Computing, 2020)
The development of technology has become more sophisticated and easily accesible, so that school inspectors are required to be creative and able to master technology in the world of education. Junior High School number 29 Pekanbaru is one of the school agencies that is facing technological problems in processing attendance data, which is still conventional using printed paper for each class to attend student attendance. In addition using gap analysis methodology is needed to find out what needs to be improved. The result of gap analysis was found that user felt the completeness of attendance data and absent data storage did not work optimally because it took a long time and the user also needed direct integration of parents about student absence in order to avoid bad behavior that occurred at school. In the end the school agency needs to improve the quality of the attendance system that is more efficient, effective and fast. After getting these problems, a system will be built to overcome the problems that occur at the school. This system will be built using the PHP programming language and MySQL as a database. For system design utilizing an incremental methodology. The incremental methodology is perfect for developers who have high turnover so that it can be done in parallel without waiting for the other stages to be completed. Data needed in this system is data relating to students, teachers at school and parents of students at home. The expected results of this system are every student absence will be sent via WhatsApp message to parents, can help teachers in making attendance and facilitate parents in monitoring student attendance at school. Testing on this system uses the gap analysis method and the test result is changes in needs that must be corrected to needs that are in accordance with what is desired is the movement of needs in quadrant 1 to quadrant 2. This shows the attendance system that is designed in accordance with the wishes of the user.